Meditation for children - Hills, John; Rozman Deborah (Millbrae Celestial arts, 1976)
A guide to meditation, individually or with the family. Includes yoga and concentration exercises.
With glossary of unusual words in text
Keywords: Children -- Religious life; Families -- Religious life; Meditation for children; Meditation